Multidetector computed tomography to predict heavy bleeding and need for angiographic embolization in patients with postpartum hemorrhage - H.M. Kim; J.Y. Lee; W.J. Seong (Clinical and Experimental Obstetrics & Gynecology)
Purpose: This retrospective study was designed to evaluate the usefulness of multidetector computed tomography (MDCT) in the identification of heavy bleeding, as a determinant of angiographic embolization (AE) in patients with postpartum hemorrhage (PPH). Materials and Methods: Fifty-seven consecutively registered patients with PPH underwent contrast-enhanced MDCT at Kyungpook National University Hospital between January 2009 and December 2012. The characteristics of the 33 patients who showed extravasation (EV) of contrast material in MDCT (EV group) were compared with those of the 24 patients who had no EV (noEV group). AE was performed in 23 out of 57 cases, based on the decision of the treating clinician. Direct localization of the bleeding site was compared with the results of MDCT. Results: A greater proportion of the EV group required AE compared with the noEV group (64% vs. 8%). The EV group showed a greater estimated blood loss (EBL) (2,100 mL vs. 1,170 mL, p < 0.001) and was associated with the need for massive blood transfusion (6 pints vs. 3 pints, p < 0.001). Disseminated intravascular coagulation was observed more frequently in the EV group (36% vs. 8%, p = 0.027). Of the 33 patients who were managed conservatively without AE, EBL after MDCT was greater in the EV group than the noEV group (410 mL vs. 45 mL, p < 0.001). The comparison of computed tomographic and angiographic findings indicated a discordant result in only 1 case. Conclusions: Contrast-enhanced MDCT is helpful to determine which patients are candidates for AE and to reduce unnecessary angiographic intervention.